The joint influence of collaboration and part-set cueing. Issue 10 (October 2014) - Kelley, Matthew R.; Pentz, Carliann; Reysen, Matthew B.
The present study was designed to examine the effects of retrieval cues on memory performance for both individuals and collaborating pairs. Participants worked either alone or together in the presence or absence of part-set cues to recall list items in Experiments 1 and 2 and to reconstruct the order of a list items in Experiment 3. The detrimental effects of collaborative inhibition were observed across all three experiments. In contrast, part-set cueing inhibition was found following free recall, whereas part-set cueing facilitation was observed on reconstruction tasks. Taken together, the results of the present experiments suggest that the effects of collaborative inhibition and part-set cueing may operate independently of one another.